Influencing factor analysis and clinical efficacy of early intervention in severe acute pancreatitis with persistent organ failure - Minchun Bu; Yun Zhang; Xiaochun Xie; Kaiming Li; Gang Li; Zhihui Tong; Weiqin Li (Scientific Reports)
Abstract This study aims to analyze the risk factors requiring early intervention in severe acute pancreatitis (SAP) patients with persistent organ failure and evaluate the clinical outcomes following treatment. This was a retrospective observational study. Inverse probability treatment weighting using propensity score methods was employed to balance baseline characteristics. Univariate and multivariate logistic regression analyses were performed to identify risk factors associated with early intervention. Smooth curve fitting was applied to explore potential relationships between variables and intervention timing. Threshold effect analysis was conducted to identify the optimal inflection point in nonlinear relationship. A total of 310 patients were included in this study. Compared to the standard treatment group (n = 162), the early intervention group (n = 148) had a higher proportion of multiple organ failure (77.1% vs. 63.6%, P = 0.021) and higher mortality (27.7% vs. 16.0%, P = 0.013), but early intervention was not significantly associated with adverse outcome (OR 1.52, 95% CI 0.71–3.26, P = 0.283). Risk factors associated with early intervention included computed tomography severity index, SOFA score, intra-abdominal pressure (IAP), and remifentanil equivalents. Among these, the SOFA score showed a negative linear relationship with intervention timing, while distinct threshold effects were observed between IAP, remifentanil equivalents, and intervention timing. One week after intervention, most patients showed improved organ function, along with reduced requirements for sedation and analgesia, as well as decreased C-reactive protein level levels and IAP (all P < 0.05). SAP patients requiring early intervention tended to have higher disease severity. Although early intervention can improve short-term organ function, reduce IAP, and lower analgesic requirements, its impact on reducing mortality remains uncertain.